Uso de los recursos tic´s y su incidencia en la enseñanza – aprendizaje de los estudiantes de octavo año de educación básica en la materia de computación de la unidad educativa “Martha Bucaram de Roldós” del cantón Yantzaza. Periodo lectivo 2013-2014. Lineamientos alternativos - Álvarez Jiménez, Dina Susana (2014)
School education since its inception was organized to educate all people equally regardless of social or economic class, so as a professional future I decided to conduct this thesis under the name USE OF TIC´s RESOURCES AND THEIR IMPACT ON THE TEACHING - LEARNING OF EIGHT YEAR STUDENTS OF BASIC EDUCATION IN THE MATTER OF EDUCATIONAL cOMPUTING UNIT "MARTHA BUCARAM DE ROLDOS" CANTON YANTZAZA. ACADEMIC YEAR 2013 – 2014; forward, has led me to develop this research project because in this educational institution does not have a proposal or guide that contributes to the use of TIC´s resources to improve the teaching - learning process, and thus qualifying as a Licensed Mention Sciences Education Computer Education at the National University of Loja. To give effect to the object that is generated using the TIC´s resources and its impact on the teaching - learning of students in eighth year of basic education in the field of computing "Martha Bucaram De Roldós" Educational Unit, was used as the inductive - inductive, scientific, statistical, likewise for data collection techniques such as the interview was used to survey teachers and students in the field of computing, after the analysis and interpretation of the data was developed, responding to the variables found, use of TIC´s resources and their impact on the process of teaching - learning. In the design and development of the proposal the results of their analysis, with the help of reliable sources of information that contribute to the realization of the proposal to serve as support for teachers and students to use was used as a basis TIC´s resources. Upon completion of this thesis project teachers are encouraged to make use of the proposal on the use of I TIC´s resources with students for the purpose of that was to know the importance of proper use of them.